2006
DOI: 10.1038/sj.npp.1301240
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Transporter 3′-UTR VNTR Genotype and ADHD: a Pharmaco-Behavioural Genetic Study with Methylphenidate

Abstract: We sought to test the hypothesis that the variable number of tandem repeat (VNTR) polymorphism in the 3 0 -untranslated region (3 0 -UTR) of the SLC6A3 gene modulates behavior in children with ADHD and/or behavioral response to methylphenidate (MPH). One hundred and fifty-nine children with AHDH (6-12 years) were assessed with regard to the Conners' Global Index for parents (CGI-Parents) and teachers (CGI-Teachers) and the response of these behaviors to MPH (0.5 mg/kg/day) using a 2-week prospective within-sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
49
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 27 publications
11
49
0
Order By: Relevance
“…58) for the homozygous 9 repeat genotype. Of note, the difference between parent and teacher ratings iand pharmacogenetic effects of DAT1 is similar to that reported by Joober et al [28].Recently, the first pharmacogenetic study of adults with ADHD reported no relationship between DAT1 genotype and response in 66 subjects titrated to a maximum methylphenidate dose of 1.3mg/kg/day [34]. However, the sample included only 3 individuals with the 9/9 genotype, and llmited statistical power to detect an effect for this genotype group.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…58) for the homozygous 9 repeat genotype. Of note, the difference between parent and teacher ratings iand pharmacogenetic effects of DAT1 is similar to that reported by Joober et al [28].Recently, the first pharmacogenetic study of adults with ADHD reported no relationship between DAT1 genotype and response in 66 subjects titrated to a maximum methylphenidate dose of 1.3mg/kg/day [34]. However, the sample included only 3 individuals with the 9/9 genotype, and llmited statistical power to detect an effect for this genotype group.…”
supporting
confidence: 74%
“…and 54mg of OROS methylphenidate [27]. Individuals homozygous for the less common 9-repeat allele demonstrated a non-linear dose-response curve, had more stimulant related side effects, and remained more impaired during treatment Similar findings were reported for the 9/9 genotype group in a double-blind, placebo controlled trial of 159 children with ADHD conducted in Montreal [28]. Although children with either the 9/10 and 10/10 genotypes displayed a significant positive response to 10 mg. of MPH, the 9/9 genotype group displayed a negative response on parent symptom ratings only ( effect size = −.…”
supporting
confidence: 68%
“…Despite their mechanistic differences, MPH and AMPH both rapidly elevate DA in the CNS and are components of the most frequently prescribed medications for ADHD, Ritalin and Adderall, respectively. The DA modulatory actions of MPH and AMPH reinforce hypotheses derived from brain imaging studies (24) and the analysis of common genetic variation (25)(26)(27)(28)(29)(30) that DA signaling perturbations contribute to risk for ADHD. Noncoding variation in the SLC6A3 gene that encodes DAT has also been associated with ADHD medication response (26)(27)(28).…”
supporting
confidence: 64%
“…The DA modulatory actions of MPH and AMPH reinforce hypotheses derived from brain imaging studies (24) and the analysis of common genetic variation (25-30) that DA signaling perturbations contribute to risk for ADHD. Noncoding variation in the SLC6A3 gene that encodes DAT has also been associated with ADHD medication response (26)(27)(28).Attention to the impact of DAT genetic variation on behavioral changes underlying mental illness was raised with the studies of Giros et al in their pioneering analysis of the DAT knockout (DAT KO) mouse (29). These investigators found that elimination of DAT expression leads to reduced presynaptic DA levels, increased extracellular DA, and profound locomotor hyperactivity in a novel environment (29), suggesting the utility of these mice as an ADHD model.…”
mentioning
confidence: 99%
See 1 more Smart Citation